تطور علم مقاصد الشريعة عبر التاريخ الإسلامي = The evolution of the discipline of the spirit of the law (Shari’ah) through Islamic history - Sari, Hannan; Mohammed Yaqub, Mohammed Abullais Shamsuddin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2018)
The discipline of Maqasid Ashari’ah, The Spirit of the Law (Shari’ah), is a body of knowledge that is both of impactful and esteemed. It has existed in some shape or form since the time of the Prophetsaw and his companionsra until the modern era. It ought to be said that this body of knowledge did not materialize with a single catalyst. In fact, it has gone through various stages of evolution until it reached its current form of a distinct body of knowledge and turned into an academic discipline. Scholars started looking at this body of knowledge academically towards the beginning of the fourth century and beyond. Among the pioneers in this field were: Imam of Al-Haramain Al-Juwaini in his book, Al-Burhan fi Usul Al-Fiqh, then Imam Al-Ghazaly in his book, Al-Mustasfa fi Usul Al-Fiqh, then Imam Al-‘Ez bin ‘Abdussalam in his book, Qawa’id Al-Ahkam fi Masaleh Al-Anam, and Ashatibi in Al-Muwafaqat, who is considered the reference in this discipline. Then came Ibn ‘Aashour in his book, Maqasid Ashari’ah Al-Islmiyah, who is considered as the leader of the discipline in the modern age. In the context of the evolution and revival of modern Islamic thought and its major Islamic disciplines, there is increasing interest in the study of the Spirit of the Law (Shari’ah) because it represents the constant within Islam and its basic doctrines and legislative principles. It comprises the basic ingredients of permanency, uniformity, and harmony of the revival of Islamic though in its myriad issues and dimensions. The interest in this field continues to rise, to the extent that you can coin the term “Spiritual Revival” in the various Islamic disciplines and thought. *********************************************************** علم مقاصد الشريعة علم عظيم الأثر جليل القدر، ووُجدت منذ عصر النبي  والصحابة والتابعين، حتى عصرنا هذا، ومقاصد الشريعة لم تظهر إلى الوجود دفعة واحدة، ولكنها مرت بمراحل متتابعة، حتى وصلت إلى مرحلة التدوين والتبويب بالصورة المعهودة الآن. ولم يبدأ النظر في المقاصد بمعناه العلمي المتعارف عليه إلا في القرن الرابع فما فوق مع ثلة من العلماء، وأبرز من كتب في هذا الفن كتابة مركزة: إمام الحرمين الجويني في كتاب "البرهان في أصول الفقه"، ثم الإمام الغزالي في كتابه "المستصفى في أصول الفقه"، ثم الإمام العز بن عبد السلام في كتابه "قواعد الأحكام في مصالح الأنام"، والشاطبي في "الموافقات" وهو العمدة في مقاصد الشريعة، ثم ابن عاشور في كتابه "مقاصد الشريعة الإسلامية"، وهو رائد مقاصد الشريعة الإسلامية في العصر الحديث، وفي إطار الجهود التجديدية والمبادرات الاجتهادية والإصلاحية للفكر الإسلامي والعلوم الإسلامية، يأتي الاهتمام المتزايد بمقاصد الشريعة الإسلامية؛ لأنها تمثل ثوابت الإسلام وأسسه العقدية والتشريعية، فهي تمثل عنصر الثبات والوحدة والانسجام لحركة الفكر الإسلامي في مختلف قضاياه وجوانبه. وما زالت العناية بمقاصد الشريعة والإقبال على طلبها في تزايد مستمر، حتى إنه يمكن اليوم التحدث عن "صحوة مقاصدية" في مجال العلوم الشرعية والدراسات الإسلامية والفكر الإسلامي.